THE INFLUENCE OF TASK-BASED LANGUAGE TEACHING (TBLT) ON ENGLISH LANGUAGE LEARNING OUTCOMES OF FOURTH GRADE STUDENTS IN SD NEGERI 201 PALEMBANG - Amidah Faridaman; Djunaidi Djunaidi; Marleni Marleni (Universitas PGRI Palembang, 2024)
This research aims to evaluate the impact of implementing the Task-Based Language Teaching (TBLT) model on the achievement of English language learning for grade IV students at SD Negeri 201 Palembang. The background to this research arises from the tendency for the learning process to be teacher-centered (one way or conventional), causing low student interest and resulting in unsatisfactory learning outcomes in class IV SD Negeri 201 Palembang. The research method used is quantitative with Quasi Experimental Design and Non-equivalent Control Group Design. Sampling was carried out using a total sampling technique on 35 class IV students at SD Negeri 201 Palembang. The results of the t-test (Independent Sample t-test) show a significance value (2-tailed) of 0.001 < 0.005, so Ha is accepted and Ho is rejected. The conclusion that can be drawn is that the application of the Task-Based Language Teaching learning model has a significant effect on the English learning outcomes of class IV students at SD Negeri 201 Palembang.